2005
DOI: 10.1007/s10899-005-9001-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Estimates of Gambling Participation and Problem Gambling among 16–18-year-old Students in Iceland: A Comparison of the SOGS-RA and DSM-IV-MR-J

Abstract: The aim of this study was to estimate gambling participation and problem gambling among Icelandic adolescents. Participants were 750 16-18-year-old students, 371 girls and 379 boys. The rate of problem gambling was estimated with the SOGS-RA and DSM-IV-MR-J. Results indicated that 96% of adolescents had gambled in their lifetime, 79% at least once in the preceding year and about 10% gamble at least once a week. A psychometric evaluation of the two screening scales revealed satisfactory reliabilities and factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 28 publications
3
28
1
2
Order By: Relevance
“…Generally, a score of four or more from the nine DSM criteria items suggests "problem" gambling; a score between 2-3 "at risk" gambling and a score between 0-1 "no problem" gambling. A recent psychometric evaluation of the Icelandic version of DSM-IV-MR-J confirmed that the scale has adequate reliability (alpha=.78) and all items loaded on one common factor (Olason et al 2006a). …”
Section: Participantsmentioning
confidence: 96%
“…Generally, a score of four or more from the nine DSM criteria items suggests "problem" gambling; a score between 2-3 "at risk" gambling and a score between 0-1 "no problem" gambling. A recent psychometric evaluation of the Icelandic version of DSM-IV-MR-J confirmed that the scale has adequate reliability (alpha=.78) and all items loaded on one common factor (Olason et al 2006a). …”
Section: Participantsmentioning
confidence: 96%
“…Through their gambling activities (online competitive games such as MMorg, online sports betting, online lotteries, cards such as solitaire and poker, online bingo, or other forms of gambling) adolescents escape into another world of fun without thought for the consequences of their behavior. Some segments of youth view gambling and gaming as a coping mechanism and a way of overcoming social isolation and idleness (Olason, Sigurdardottir, & Smari, 2006). The most common perceived benefits of gambling are suggested to be social enhancement, financial gain, and positive changes in affect=mood.…”
Section: Online Gambling and Experiential Aspectsmentioning
confidence: 99%
“…For adolescents gambling is about playing (Olason et al, 2006). Perceived availability, perceived risk, and perceived benefits are significant predictors of regular gambling.…”
Section: Online Gambling and Experiential Aspectsmentioning
confidence: 99%
“…In the U.S. and Canada, findings suggest that approximately 15.3 million 12-17 year olds have been gambling, while 2.2 million are reported to be experiencing serious gambling related problems. Increased levels of gambling among adolescents have been reported in North America, Europe, Asia, Australia, New Zealand and Iceland (Abbott and Volberg 2000;Azmier 2000;Fisher 1993;Griffiths 1995;Derevensky 1998 National Research Council 1999;Olason et al 2006) with between 4-8% of youth experiencing pathological patterns of gambling and 10-15% at risk for the development of gambling problems (Shaffer and Hall 1996). With increases in the availability, accessibility and participation in gambling activities, the problems that youth gamblers are facing are likely to increase.…”
Section: Mark Griffiths and Sue Fisher In The United Kingdom And Duramentioning
confidence: 99%